(untitled) (Siddhanta’s International Journal of Advanced Research in Arts & Humanities, 2025)
The COVID-19 pandemic fundamentally altered intimate relationships and family structures worldwide, creating unprecedented challenges and opportunities for connection in both physical and digital spaces. This paper examines how couples, families, and individuals have navigated intimacy during and after the pandemic, analyzing the emergence of hybrid relationship models that blend in-person and virtual interactions. Through analysis of survey data, interview findings, and relationship outcome studies, we explore three primary areas: (1) the transformation of romantic partnerships under social distancing measures, (2) the evolution of family dynamics in remote work and learning environments, and (3) the development of new intimacy practices mediated by technology. Findings reveal that while initial pandemic restrictions created significant relationship stress, many couples and families developed enhanced communication skills, deeper emotional bonds, and more intentional relationship practices. The post-pandemic era has witnessed the emergence of "hybrid intimacy" – a new paradigm where digital and physical connection complement each other in sustainable ways. These changes have implications for relationship counseling, family therapy, and social policy moving forward.